Adherence to Practice of Mindfulness in Novice Meditators: Practices Chosen, Amount of Time Practiced, and Long-Term Effects Following a Mindfulness-Based Intervention - Ribeiro, Letícia (Mindfulness (N Y), 2017)
In this study, we objectively tracked the duration, frequency, and the preferred practices chosen by novice mindfulness practitioners following a mindfulness meditation (MM) intervention. A sample of 55 mildly stressed participants, aged 50 to 80 years old, underwent an individual 6-week MM intervention and had their guided meditation home practice electronically recorded during the intervention and the 8-week post-intervention period. Participants’ psychological well-being was assessed through self-report measures of mindfulness, quality of life, and symptoms of depression and stress. Results evidenced a high adherence to practice, with an average of ~23 minutes per day during the intervention and ~16 minutes per day in the follow-up period. Body scan, sitting meditation, and breathing space were the most popular meditation practices among participants. Our results showed significant alterations in self-reported measures over time, suggesting improvements in stress and overall quality of life. Changes in the self-report measures did not correlate with MM practice time, which suggests that other psychological phenomena, including quality of meditation practice, influence these outcomes.